2023
DOI: 10.1186/s13071-023-05666-8
|View full text |Cite
|
Sign up to set email alerts
|

Molecular identification and genetic characteristics of Cryptosporidium spp., Giardia duodenalis, and Enterocytozoon bieneusi in human immunodeficiency virus/acquired immunodeficiency syndrome patients in Shanghai, China

Abstract: Background Opportunistic infections are a ubiquitous complication in human immunodeficiency virus (HIV)/acquired immunodeficiency syndrome (AIDS) patients. Cryptosporidium spp., Giardia duodenalis, and Enterocytozoon bieneusi are common opportunistic intestinal pathogens in humans. In China, despite the number of HIV/AIDS patients being extremely large, only a few studies have investigated opportunistic infections caused by intestinal pathogens in this patient population. The aims of this study… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
6
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
9

Relationship

2
7

Authors

Journals

citations
Cited by 21 publications
(6 citation statements)
references
References 75 publications
0
6
0
Order By: Relevance
“…In China, genotypes D and EbpC have been detected in humans and numerous wild, domestic, and companion animals from 26 provinces/municipalities [35]. Meanwhile, human E. bieneusi infection cases caused by genotypes D and EbpC were ranked first and second, respectively [13]. In addition, we also identified zoonotic genotypes Peru 8 (syn.…”
Section: T C T G a T G T A C T G T T G T C G C T Gmentioning
confidence: 84%
“…In China, genotypes D and EbpC have been detected in humans and numerous wild, domestic, and companion animals from 26 provinces/municipalities [35]. Meanwhile, human E. bieneusi infection cases caused by genotypes D and EbpC were ranked first and second, respectively [13]. In addition, we also identified zoonotic genotypes Peru 8 (syn.…”
Section: T C T G a T G T A C T G T T G T C G C T Gmentioning
confidence: 84%
“…Despite the scarcity of data on C. parvum gp60 subtypes in the population of China, the existing evidence has substantiated the ability of the IIdA19G1 subtype to infect human beings [ 13 , 34 ]. Moreover, this particular subtype has been identified in children and individuals afflicted with AIDS in China [ 13 15 , 35 ]. Simultaneously, it is observed that the prevalence of C. parvum infection in animals originating from China is extensive, with a notable abundance of gp60 subtypes.…”
Section: Discussionmentioning
confidence: 99%
“…Cryptosporidium spp., Giardia duodenalis , and Enterocytozoon bieneusi are among the most common diarrhea-causing pathogens with a global distribution in humans and livestock. These intestinal protozoans can lead to severe chronic diarrhea, malnutrition, and sometimes even death in immunocompromised or deficient hosts [ 1 ]. The (oo)cysts/spores produced by these protozoans are widely distributed in the environment after they are excreted with the feces of hosts.…”
Section: Introductionmentioning
confidence: 99%